2019
DOI: 10.1021/acs.iecr.9b03472
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Metal Separations Using Hydrophilic Ionic Liquids and Analogues as Complexing Agents in the More Polar Phase of Liquid–Liquid Extraction Systems

Abstract: The separation of metals by liquid–liquid extraction largely relies on the affinity of metals to the extractants, which normally reside in the organic (less polar) phase because of their high hydrophobicity. Following a different route, using aminopoly(carboxylic acid)s (e.g., EDTA) as complexing agents in the aqueous (more polar) phase was found to enhance metal separations by selectively complexing metal cations. In this study, we demonstrate that, hydrophilic ionic liquids and analogues in the more polar ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
0
16
2
Order By: Relevance
“…The classification by Chauvin of some of the anions in ionic liquids as highly coordinating or weakly coordinating are in excellent agreement with the ordering of their coordinating ability indices, and the wide choice of anions presented in Table should allow researchers to select alternative anions with stronger or weaker coordinating abilities than those currently used in ionic liquids, as a given application may require. For instance, Li et al . found that the different extraction properties of Co II and Sm III salts with different ionic liquids was not affected by their cation, but could be attributed to the different coordinating abilities of the anions towards transition metals and lanthanides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification by Chauvin of some of the anions in ionic liquids as highly coordinating or weakly coordinating are in excellent agreement with the ordering of their coordinating ability indices, and the wide choice of anions presented in Table should allow researchers to select alternative anions with stronger or weaker coordinating abilities than those currently used in ionic liquids, as a given application may require. For instance, Li et al . found that the different extraction properties of Co II and Sm III salts with different ionic liquids was not affected by their cation, but could be attributed to the different coordinating abilities of the anions towards transition metals and lanthanides.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Li etal. [93] found that the different extraction properties of Co II and Sm III salts with different ionic liquidsw as not affected by their cation, but could be attributed to the different coordinating abilities of the anions towards transition metals and lanthanides. Althoughm ost anionsu sed in ionic liquids show no significant (eco)toxicological effects, somefluorinated anions do presenta strong effect, and their biodegradability is another aspect to consider when selectinga na nion.…”
Section: àmentioning
confidence: 98%
“…9 Recently, a series of non-aqueous SX systems have been investigated and several enhanced separations have been obtained. [10][11][12][13][14][15] The substitution of water by polar organic solvents changes the solvation of metal cations in the polar solvent, and the relative solubility of the complexes between the two immiscible phases also affects the extraction equilibrium. 15 The extraction of metals from polar organic solvents can be significantly altered by changing polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polar solvents instead of water in the extraction of metals is called non‐aqueous solvent extraction (NASX) 9 . Recently, a series of non‐aqueous SX systems have been investigated and several enhanced separations have been obtained 10‐15 . The substitution of water by polar organic solvents changes the solvation of metal cations in the polar solvent, and the relative solubility of the complexes between the two immiscible phases also affects the extraction equilibrium 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This observations can be explored for the development of more efficient solvent extraction processes, as illustrated in recent papers. [38][39][40][41][42] In this paper, an efficient non-aqueous solvent extraction process for separation of indium and zinc from an ethylene glycol (EG) feed solution is described. The quaternary phosphonium ionic liquid trihexyl(tetradecyl)phosphonium chloride (Cyphos IL 101) and the quaternary ammonium ionic liquid Aliquat 336 (a mixture of tri-n-octylmethyl and tri-ndecylmethylammonium chloride with the former dominating) are used as extractants due to their commercial availability.…”
Section: Introductionmentioning
confidence: 99%